Existence of strictly positive solutions for sublinear elliptic problems in bounded domains - Godoy, Tomás Fernando; Kaufmann, Uriel (2021)
Fil: Godoy, Tomás Fernando. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.